Canva Application-Based Learning Media on Motivation and Learning Outcomes - Rinja Efendi; Hasibuan, Abdul Putra Ginda; Elvina; Siregar, Pariang Sonang (Universitas Pendidikan Ganesha, 2023)
Low learning outcomes can be influenced by the use of learning media that is less than optimal and low student learning motivation. This study aims to analyze the effect of the Canva application-based learning media on motivation and learning outcomes. This type of research is quantitative correlational and regression. The subjects in this study were 107 high school students. The Slovin formula was used to determine the sample size, so 84 students were obtained. The data collection method uses a Likert scale questionnaire. The method of data analysis is carried out quantitatively/statistically. The study results show that the Canva application-based learning media affects motivation and learning outcomes. Thus it is known that the Canva application-based learning media affects motivation and learning outcomes. The solution that can be done to improve learning outcomes is to increase learning motivation and use appropriate learning media. This research can provide understanding to teachers in using learning media and motivate them to learn to improve student learning outcomes.